Çağdaş sanatta ataerkil failin imgesi - Kahraman, Ayşe Tülay (My University, 2021)
Çağdaş sanatta birçok açılımın yanı sıra toplumsal cinsiyetin inşası ve kimliklerin oluşumuyla ilgili yapıtların sayılarında da artış olmuştur. Büyük söylemlerin mercek altına alındığı bu dönemde ataerkilliğin eleştirisi genellikle Feminist Sanatın konusu olarak gündeme gelir. Şiddeti ele alan birçok sanat yapıtı kurbanın yanı sıra failin özelliklerini de betimler. Bu çalışma ile failin ataerkil özellikleri incelenmeye çalışılmıştır. Genel olarak failin özelliklerinin belirgin olduğu betimlemelerde şiddetin daha gizli olduğu görülmüştür. Ayrıca sanatçılar imgeleri yeniden üreterek faili veya kurbanı tanımlarken şiddeti betimleyen fail konumuna geçmektedir.

In addition to many subjects in contemporary art, there is an increase in the number of works related to the construction of gender and the formation of identities as well. While major discourses are under the spotlight, the critique of patriarchy usually comes to the fore as a subject of Feminist Art. Many artworks dealing with violence depict the characteristics of the perpetrator as well as the victim who is exposed to violence. In this study, the patriarchal characteristics of the perpetrator are tried to be examined. It seems that violence is more hidden in the descriptions where the characteristics of the perpetrator are evident. Furthermore, artists become perpetrators in reproducing the image of the perpetrator or victim while describing the violence.
Keywords: Artist as a Perpetrator; Arts, Modern; Ataerkil Fail İmgesi; Cinsiyet ayrımı; Erkeklik Violence in Art; Fine arts education; Güzel sanatlar eğitimi; Masculinity; Patriarchal Perpetrator Image; Sanatçı Fail; Sanatlar, Modern; Sanatta Şiddet; Sex discrimination